Assessing Crime Vulnerability Levels in Balikpapan City - Rahmat Aris Pratomo; Nadia Almira Jourdan; Dwiana Novianti Tufail; Ogamaliel Sohmo Sinamo; Deka Adam Budiman; Ajeng Meidiany Putri (Journal of Applied Sciences, Management and Engineering Technology, 2026)
Crime is a social issue with far-reaching impacts on community security and quality of life, including in Balikpapan City, the largest city in East Kalimantan, with a population of 704,110 in 2022. Despite being an economic hub with significant contributions in the oil, gas, and trade sectors, Balikpapan faces serious challenges in creating a safe environment, marked by high crime rates and an increase in cases such as theft, assault, and drug-related crimes. This heightened vulnerability is influenced by social, economic, and environmental factors, such as social inequality, unemployment, and low legal awareness. To address these challenges, in-depth assessments and crime mapping are essential to formulating effective prevention strategies and efficiently allocating resources. This study aims to assess the crime vulnerability levels in Balikpapan City through a spatial approach using Kernel Density analysis. This method estimates spatial density based on crime incident locations recorded in 2022-2023, sourced from the Balikpapan Police Department. The data were categorized into five vulnerability levels to produce detailed distribution maps and crime vulnerability levels, aiding in identifying crime distribution patterns in the city. The classification of crime vulnerability levels in Balikpapan City based on Kernel Density analysis reveals areas of very high vulnerability concentrated in Balikpapan Kota, Balikpapan Tengah, and Balikpapan Selatan districts, with dominance in Balikpapan Kota. High vulnerability levels surround very high vulnerability areas and are distributed across the same three districts. Moderate vulnerability levels extend across five districts, covering Balikpapan Kota, Tengah, Selatan, Barat, and Utara. Low and very low vulnerability levels are scattered across all districts, with Balikpapan Barat largely falling into the very low category.